Teacher approaches to writing in science in bilingual elementary classrooms. Issue 8 (14th September 2021) - Roper, Soleil; Carpenter, Daniel; Garza, Esther
ABSTRACT: This investigation examined the approaches bilingual education elementary teachers implemented to develop student science and English language understanding. In this investigation, teachers used Proficiency Level Descriptors (PLDs) to assess bilingual-ELs' (BLs) English writing understanding. Teacher interviews, student writing samples, and the collection of artifacts, such as student blog entries were collected as data sources. The findings indicate that teachers have a strong commitment to develop bilingual and bi-literacy competence, build background knowledge, and make connections between home and school. In addition, teachers were found to perceive science and language learning as separate entities and failed to provide evidence of the implementation of the PLDs in science writing as an ongoing assessment.